Results from a nationwide postmarketing cohort study of patients in Sweden treated with etanercept. Issue 2 (18th June 2004) - Feltelius, N; Fored, C M; Blomqvist, P; Bertilsson, L; Geborek, P; Jacobsson, L T; Lindblad, S; Lysholm, J; Rantapää-Dahlqvist, S; Saxne, T; Klareskog, L
Abstract : Objectives: To describe a nationwide system for postmarketing follow up of new antirheumatic drugs in Sweden, and to analyse safety and effectiveness in an etanercept treated patient cohort. Methods: Etanercept became available in Sweden for prescribing on a named patient basis in 1999. All patients treated were included in a follow up of intensified adverse event reporting and recording of clinical outcome during 24 months, according to the EULAR core set. Results: The mean (SD) disease activity score (DAS 28) value at inclusion among 820 patients recruited on a named patient basis during year 1 was 5.99 (1.19). After two years, 21% (n = 172) of these patients had discontinued the treatment. Of the remaining 648 patients, 68% (n = 442) responded to the treatment. However, in 55% of the responders, the disease activity was intermediate or high (mean DAS 28, 3.37 (1.20)). In all, 540 adverse events were reported in 421 adverse drug reaction (ADR) reports, in 294 patients. The events in 80 reports (19%) were serious. Twenty two per cent of the events were infections, of which 24% (n = 29) were serious. The incidence of serious adverse events remained constant over time. Conclusions: At start of etanercept treatment, patients had high disease activity. Activity remained high in a large proportion of the responding patients. Although serious ADRs occurred during late phases of treatment, no unexpected safety problems arose. No specific indicators of ADR risk were found. The monitoring system that was established may be useful in future postmarketing surveillance.